Strengthening Cross-Madrashab Fiqh Literacy and Religious Moderation through Routine Islamic Studies at the Al Barakah Mosque, Permata 2 Housing Complex, Bekasi City - Didi Darmadi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Urban Muslim communities today face various challenges in understanding differences in religious opinions, particularly in fiqh issues that often lead to fanaticism and a lack of tolerance toward diverse religious practices. This community service program aims to enhance Comparative Fiqh literacy while strengthening religious moderation through regular Islamic study sessions conducted at Al Barakah Mosque, Permata 2 Residential Area, Bekasi City. The method employed in this community service program was a Participatory Action Research (PAR) approach integrated with qualitative research methods. The program was implemented through regular study sessions, interactive discussions, and guided learning on fiqh from the perspectives of the four major schools of Islamic jurisprudence. The results indicate a significant improvement in participants’ understanding of the diversity of scholarly opinions, the development of a more tolerant attitude toward different religious practices, and increased awareness of the importance of religious moderation in social life. Comparative Fiqh studies have proven to be an effective means of fostering a culture of dialogue, reducing exclusivist attitudes, and strengthening Islamic brotherhood (ukhuwah Islamiyah) within urban communities. Furthermore, the program has reinforced the role of the mosque as a center for inclusive and moderate Islamic education and community development.